Rapid progression to cardiac tamponade in Erdheim–Chester disease despite treatment with interferon alpha. Issue 4 (3rd July 2016) - Nakhleh, Afif; Slobodin, Gleb; Elias, Nizar; Bejar, Jacob; Odeh, Majed
Abstract : Erdheim–Chester disease (ECD) is a rare form of non-Langerhans histiocytosis with heterogeneous clinical manifestations. The most common presentation is bone pains typically involving the long bones. Approximately 75% of the patients develop extraskeletal involvement. Cardiac involvement is seen in up to 45% of the patients, and although, pericardial involvement is the most common cardiac pathology of this rare disease, cardiac tamponade due to ECD has been very rarely reported. We describe a case of a patient found to have ECD with multi-organ involvement and small pericardial effusion, which progressed to cardiac tamponade despite treatment with interferon alpha.